MONOCLONAL-ANTIBODIES SPECIFIC FOR MERCURIC IONS - (:unkn) unknown (NATL ACAD PRESS, 1992)
Monoclonal antibodies (mAbs) that react with soluble mercuric ions have been produced by injection of BALB/c mice with a hapten-carrier complex designed to maximize exposure of the metal to the immune system. Three hybridomas producing antibodies that reacted with bovine serum albumin (BSA)-glutathione-HgCl, but not with BSA-glutathione, were isolated from the spleen of a mouse given multiple injections with glutathione-HgCl conjugated to keyhole limpet hemocyanin. Stable subclones were established from two of these antibodies, designated mAb 4A10 and mAb 1F10. The binding of both antibodies to immobilized BSA-glutathione-HgCl was inhibited by soluble HgCl2, and dissociation constants for mercuric chloride binding were 2.3 and 3.7 nM for mAbs 4A10 and 1F10, respectively. Both antibodies bound mercuric acetate with similar affinities, demonstrating that the antibodies were capable of binding to mercuric ions in the presence of a different counterion than the one used in the immunogen. Reactions were not observed with other metal cations by either antibody. These data demonstrate the successful induction of antibodies that react very specifically with mercuric ions in solution regardless of the presence of a carrier.
Keywords: HYBRIDOMAS; METALS; BINDING; COMPLEXES; EPITOPE; ANTIGEN; ZINC; SITE